Oxaloacetate reduces emotional symptoms in premenstrual syndrome (PMS): results of a placebo-controlled, cross-over clinical trial - Lisa Tully; John Humiston; Alan Cash (Korean Society of Obstetrics and Gynecology, 2020)
ObjectivePremenstrual syndrome (PMS) affects millions of women. While over-the-counter products have helped with the physical symptoms of PMS, emotional symptoms have been less well supported. The objective of this trial was to measure the effect of an oxaloacetate/vitamin C combination on the major emotional symptoms of PMS, including depression, anxiety, perceived stress, aggression, and suicidal ideation.MethodsForty-eight women experiencing PMS completed a baseline survey comprising the Beck's Depression Inventory, Cohen Perceived Stress Scale, Generalized Anxiety Disorder Test, and Buss-Perry Aggression Questionnaire. After baseline measurements, participants were randomly assigned to take either 2 capsules of 100 mg oxaloacetate/150 mg ascorbic acid, or 2 capsules of rice flour (placebo) for their entire menstrual cycle. At menstruation, the women completed the 4 surveys again. The women then switched capsules in a cross-over design and continued the study for an additional menstrual cycle. The final assessment was repeated at menstruation. Statistical analysis of the 4 surveys was performed to examine efficacy.ResultsOxaloacetate/vitamin C supplementation during PMS significantly improved depression, perceived stress, anxiety, aggression, and suicidal ideation. The mean improvement in depression was 54.1%, 35.8% for perceived stress, 51.43% for generalized anxiety, and 17.8% for aggression. Suicidal ideation was reduced by 47.9%. All results were highly significant.ConclusionA combination of oxaloacetate and vitamin C supplementation helped to alleviate depression, anxiety, perceived stress, aggression, and suicidal ideation symptoms associated with PMS.Trial RegistrationClinicalTrials.gov Identifier: NCT03509714